Determinansi Work Life Balance dan Self Efficacy Terhadap Kinerja Tenaga Kesehatan Puskesmas pada Provinsi Sulawesi Selatan - Hendra Gunawan (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2023)
This study aims to analyze the determinants of work life balance and self-efficacy on the performance of health workers in the city of South Sulawesi province, both partially and simultaneously. This research is an explanatory research using a quantitative approach and data collection techniques through questionnaires and observation. The population in this study was 120 puskesmas health workers in the province with a sampling technique using simple random sampling where the population was sampled regardless of criteria from the entire population with a total sample of 120 health workers. Hypothesis testing using SPSS tools. The findings of this study are positive significant variable measurements where direct testing shows work life balance and good self-efficacy towards performance have a positive and significant influence.